A folate-conjugated platinum porphyrin complex as a new cancer-targeting photosensitizer for photodynamic therapy. Issue 21 (20th May 2019) - Yang, Mengqian; Deng, Jingran; Guo, Ding; Zhang, Jie; Yang, Lixia; Wu, Fengshou
Abstract : A new folate-conjugated platinum porphyrin complex was synthesized, which displayed high singlet oxygen quantum yield and strong targeting ability. Abstract : A new folate-conjugated platinum porphyrin complex (Por 4) was synthesized and characterized. The singlet oxygen production of the conjugates was evaluated through a 1, 3-diphenylisobenzofuran method. The targeting ability and subcellular localization of Por 4 were confirmed by confocal laser scanning microscopy in HeLa cells (overexpression of FR) as well as in A549 cells (low expression of FR). The results suggested that the modification of the carboxyl group with a porphyrin compound did not decrease the binding affinity of folic acid to FR positive cancer cells. Moreover, the MTT assay using HeLa cells and A549 cells verified the low cytotoxicity of Por 4 in the dark. Upon irradiation, Por 4 showed noticeable improvement in toxicity against cancer cells with the overexpression of FR. Upon the treatment of Por 4 at the concentration of 20 μM, the cell viability was determined as 22% and 75% for HeLa and A549 cells, respectively, indicating that the folate-conjugated platinum porphyrin complex could be a promising PDT agent for cancer with overexpression of the folate receptor.